Vertical and horizontal misfit analysis of 3-unit FDP fabricated with different techniques and CAD/CAM systems - Pellizzer, Eduardo Piza [UNESP]; de Mello, Caroline Cantieri [UNESP]; Gomes, Jéssica Marcela de Luna [UNESP]; Santiago Júnior, Joel Ferreira; Lemos, Cleidiel Aparecido Araújo [UNESP]; Verri, Fellippo Ramos [UNESP] (FapUNIFESP (SciELO), 2018)
The aim of this is was evaluate the vertical and horizontal marginal adaptation of 3-unit fixed partial denture frameworks fabricated using different techniques and CAD/CAM systems. A total of 40 framework specimens were fabricated and divided into four groups as follows: lost-wax casting (G1); lost-wax casting with welding (G2); extraoral optical scanning of models (3S/DWOS) (G3); intraoral optical scanning (Cerec Bluecam/Sirona) (G4). A reference model was used to simulate a fixed partial denture with three elements (with a central pontic). The frameworks of G1 and G2 were cast in nickel-chromium (NiCr) alloy, whereas those of G3 and G4 were milled in zirconia. In all groups, vertical and horizontal marginal adaptation (over-contour and under-contour) was evaluated using a three-dimensional optical microscope (Quick Scope, Mitutoyo). The results showed higher vertical marginal misfit in G1 than in the other groups (p<0.001). Regarding horizontal marginal misfit, higher over-contour values occurred in G3 than in the other groups (p<0.001). G3 did not show under-contour at all, whereas the other groups did not differ from each other in this regard (p>0.05). Within the limitations of this study, it can be concluded that lost-wax casting with welding is a viable alternative to the use of CAD/CAM systems to fabricate frameworks of three-unit FPDs, since the techniques yielded similar vertical misfit values. Extra-oral CAD/CAM systems showed the highest horizontal misfit (over-contour) compared to other groups.
Keywords: CAD/CAM; Dental soldering; Marginal adaptation; Misfit; Welding